Combination of Implementation of Antiphase and Overcurrent Relays for Protection of 0.75 kW Three-Phase Induction Motor in Industry - Tri Atmojo, Purbo Widagdo; Amirullah, Amirullah (ELKHA : Jurnal Teknik Elektro, 2024)
Three-phase induction motors are the most widely used type of motor in industry. These motor operations are generally susceptible to unbalanced voltage disturbances. This interference is caused by the loss of one or two phases on the input side of the motor. This source voltage disturbance then causes an unbalanced current which flows to the coil, causing a phase shift, overheating the coil, and if left for a long time, it causes the motor to burn out. The research aims to design and implement a combination of antiphase relay (APR) and overcurrent relay (OCR) to prevent voltage drops due to failure of one or two phases and overcurrent to prevent overheating and fires in three-phase induction motor coils. Motor testing is carried out by adjusting the magnitude of the three-phase motor source voltage in three testing stages, i.e., tests A, B, and C, under no-fault conditions, 1-phase open and 2-phase open conditions respectively. The direct test results are then validated with ETAP simulations. In direct testing, A, B, and C can produce a current and relay working time of 6 A-31.04 s, 7.1 A-20.98 s, and 8.3 A-14.93, respectively. Meanwhile, testing using ETAP simulation can produce current and relay working times of 6A-31.366 s, 7A-20.599 s, and 8A-14.822 s respectively. The combination of an APR and an OCR can detect and interrupt voltage drops and overload currents in systems connected to 0.75 kW three-phase induction motors in the industry.